2009
DOI: 10.1002/eji.200838807
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stable human Treg and Th clones by transcriptional profiling

Abstract: From cancerous and non-cancerous patients, we derived stable clones of CD4 1 Treg, defined as clones that expressed high CD25 at rest, were anergic in vitro, and suppressed the proliferation of co-cultured CD4 1 cells. A conserved region of FOXP3 intron 1 was demethylated in all Treg clones, whereas it was methylated in non-regulatory Th and CTL clones. In our panel of human clones, this stable epigenetic mark correlated better with suppressive activity than did FOXP3 mRNA or protein expression. We used expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 52 publications
3
104
2
Order By: Relevance
“…4 shows that stimulation of activated CD25 þ cells with L. infantum or P. falciparum extracts, in the absence of any support of external TGF-b, induces phosphorylation of SMAD 2/3 proteins. In contrast, the same parasitic extracts do not activate SMAD 2/3 phosphorylation in activated CD25 À cells which express TGF-b receptor but do not express membranebound latent TGF-b [29,30].…”
Section: Effect Of Parasitic Extracts On the Activation Of Membrane-bmentioning
confidence: 80%
See 1 more Smart Citation
“…4 shows that stimulation of activated CD25 þ cells with L. infantum or P. falciparum extracts, in the absence of any support of external TGF-b, induces phosphorylation of SMAD 2/3 proteins. In contrast, the same parasitic extracts do not activate SMAD 2/3 phosphorylation in activated CD25 À cells which express TGF-b receptor but do not express membranebound latent TGF-b [29,30].…”
Section: Effect Of Parasitic Extracts On the Activation Of Membrane-bmentioning
confidence: 80%
“…TGF-b plays a key role in maintaining the balance between immunoprotection mediated by T cells and immunopathology either in experimental models of malaria and toxoplasma infection and in human diseases [5,29,30]. Macrophages and dendritic cells mostly account for TGF-b production following parasite uptake; nevertheless, the production of these cytokines by activated CD4 þ T cells following a direct stimulation with parasites or parasite products has also been reported [10,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…The converted DNA was then analyzed by real-time PCR for the methylated and the unmethylated forms of Foxp3 intron 1 as described previously (22). The results are expressed as percentages of unmethylated Foxp3 sequences, calculated as follows: % of demethylation = 2 ΔCt /(1 + 2 ΔCt ), wherein ΔCt = (Ct with methylated primers) 2 (Ct with unmethylated primers).…”
Section: Foxp3 Intron 1 Demethylation Analysis Of Cd4 + T Cell Clonesmentioning
confidence: 99%
“…Analyzing their transcriptional profiles, we demonstrated that activated human Tregs, but not other T cells, produced active TGF-ß1. 2 A possible contribution of soluble TGF-ß1 to immunosuppression by Tregs was in line with the fatal autoimmune phenotype of Tgfb1 -/-mice, but not with the contact dependency of immunosuppression by Tregs. But then we observed that TGF-ß1-signaling in T cells co-cultured with Tregs was also contactdependent, suggesting that active TGF-ß1 was produced close to the Treg surface.…”
mentioning
confidence: 81%
“…But then we observed that TGF-ß1-signaling in T cells co-cultured with Tregs was also contactdependent, suggesting that active TGF-ß1 was produced close to the Treg surface. 2 This prompted us to study the mechanisms of TGF-ß1 activation by Tregs. Indeed, most cells produce inactive forms of TGF-ß1 but very few activate the cytokine, via tightly regulated mechanisms that are cell-type specific.…”
mentioning
confidence: 99%